Interlingual Interference in Multilingual Students: An Optimality Theory Approach - Dedy Suhery; Cut Intan Meutia; Mohd Hamid Raza; Zahratul Idami (RETORIKA: Jurnal Ilmu Bahasa, 2023)
In Indonesia, multilingualism is a common phenomenon, where individuals regularly switch between multiple languages and dialects in their daily communication. Within this multilingual environment, people often learn several words from their second (L2) or third (L3) language alongside their native tongue (L1). This study aims to investigate the primary linguistic features affected by interlingual interference among multilingual learners at IAIN Langsa and how the principles of Optimality Theory can help explain the observed patterns of interlingual interference in the language learning processes of these students, specifically those in the Arabic Education Department. To address these questions, the research focuses on the language spoken by multilingual learners proficient in Acehnese, Bahasa Indonesia, and Arabic at IAIN Langsa. Data collection involved fieldwork, interviews, and recordings, with five students as the research subjects. The study results indicate that interlingual interference has a multifaceted impact on multilingual learners in the Arabic Education Department at IAIN Langsa. The findings demonstrate that Acehnese phonology influences the development of Arabic words. This is evident in how Acehnese-Arabic speakers modify the final phoneme /d/ to /t/ in three words: [a.had] becomes [a.hat], [ah.mad] becomes [ah.mat], and [mau.lid] changes to [mo.lit]. Multilingual learners may transfer pronunciation patterns, intonation, and accent elements from their native languages into the target language, resulting in pronunciation difficulties and challenges in acquiring the phonological system of the target language.